Modelling Inclusive Knowledge Systems and Leadership Effects on Teacher Outcomes in Bogor’s Inclusive Primary Schools: A SEM-PLS and IPMA Study - Gugun Nugraha; Furqon Syarief Hidayatulloh; Elisa Anggraeni (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study investigates the moderating roles of both managerial and community-based inclusive leadership in how an inclusive knowledge system—covering acquisition, dissemination, and utilisation—influences teacher satisfaction and motivation in inclusive primary schools. Conducted in Bogor City, one of West Java's cities with the highest number of students with special needs, the research was carried out from August 2024 to July 2025. Data were collected through a validated questionnaire from participants selected via purposive sampling, including 100 inclusive educators, 10 inclusive school principals, and an expert from the Education Office of  Bogor City, to develop strategic recommendations. Quantitative data were analysed using SEM-PLS and IPMA (with SmartPLS 4 Software). Findings reveal that Teacher Satisfaction was significantly affected by all knowledge systems and managerial inclusive leadership, while Teaching Motivation was influenced only by Knowledge Acquisition and managerial inclusive leadership (p<0.05). Managerial Inclusive Leadership significantly moderated Knowledge Dissemination but did not moderate Knowledge Acquisition and Utilisation at all. Community Inclusive Leadership significantly moderated the effects of Knowledge Dissemination on Teaching Motivation and of Knowledge Acquisition on Teacher Satisfaction. Another important finding is that Teacher Satisfaction does not have a significant effect on Teaching Motivation (p-value = 0.228 > 0.05). IPMA results emphasise that Knowledge Dissemination, Acquisition, and  Managerial Inclusive Leadership are essential but require support due to their weak performance. The study recommends practical steps for the education office and inclusive schools to implement policies and provide facilities that promote knowledge sharing and improve the competence of inclusive educators.